(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Vietnamese economy is increasingly integrated into the worldand constantly changing. The process has created opportunities but also posed many difficulties and challenges. Local enterprises with the goal of sustainable development overcome the difficulties and competitive pressure of the economy have been searching for effective management tools that assist them in making decisions in general and strategic decisions in particular. One of the key management tools is strategic management accounting (SMA). SMA is considered an effective governance tool to provide strategic information to help managers make strategic decisions to enhance management, gain competitive advantages and reduce risks from the business environment of the unit. Therefore, SMA strengthens sustainable development of enterprises in integration stage. However, the application of SMA in enterprises depends on many internal and external factors. By reviewing previous research, the findings show that the application of SMA in Vietnamis influenced by 7 factors including: (1) Management decentralization, (2) Company size, (3) Business strategy, (4) Accountant qualifications, (5) Technology level, (6) Competition and (7) Perceived environmental uncertainty. In addition, the author also have outlined the limitations that the study still has and the direction of the next study.